Costal2, a novel kinesin-related protein in the Hedgehog signaling pathway. - Sisson, J.C.; Ho, K.S.; Suyama, K.; Scott, M.P. (Cell, 1997)
The Hedgehog (HH) signaling proteins control cell fates and patterning during animal development. In Drosophila, HH protein induces the transcription of target genes encoding secondary signals such as DPP and WG proteins by opposing a repressor system. The repressors include Costal2, protein kinase A, and the HH receptor Patched. Like HH, the kinase Fused and the transcription factor Cubitus interruptus (CI) act positively upon targets. Here we show that costal2 encodes a kinesin-related protein that accumulates preferentially in cells capable of responding to HH. COS2 is cytoplasmic and binds microtubules. We find that CI associates with COS2 in a large protein complex, suggesting that COS2 directly controls the activity of CI.